Mass Transfer Problem with Saturation Limit on Graph - Kolesnykov, Valerii; Klyushin, Dmytriy (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This paper contains main results of the research of mass transfer problem in porous medium with saturation limit on graphs. The equation that describes this problem is based on the one-dimensional Richards-Klute equation with additional mass balance equations. Among the results are existence theorem, stability result and effective numerical method for solving equation.